Thriving at work as a mediator of the relationship between psychological resilience and the work performance of clinical nurses - Zhou-Min Shen; Yang-Yang Wang; Yi-Min Cai; Ai-Qun Li; Yu-Xin Zhang; Hong-Jiao Chen; Yuan-Yuan Jiang; Juan Tan (BMC, 2024)
Abstract Objective This study aims to investigate the relationship between psychological resilience, thriving at work, and work performance among nurses, as well as analyse the mediating role of thriving at work in the relationship between psychological resilience and the work performance of nurses. The findings are intended to serve as a reference for nursing managers to design tailored work performance intervention programs. Method Using convenience sampling, 308 clinical nurses were selected from a tertiary hospital in Changsha City, Hunan Province, China, from February to April 2023. The Connor-Davidson Resilience Scale (CD-RISC), the Thriving at Work Scale, and the Work Performance Scale were employed for the questionnaire survey. Pearson correlation analysis was used to explore the relationship between psychological resilience, thriving at work and work performance. The SPSS 26.0 software's 'Process' plugin was utilised for mediation effect analysis. Results Significantly positive correlations were found between psychological resilience and thriving at work (r = 0.806, P < 0.01), thriving at work and work performance (r = 0.571, P < 0.01) as well as psychological resilience and work performance (r = 0.572, P < 0.01). Psychological resilience significantly predicted work performance positively (β = 0.558, t = 11.165, P < 0.01), and this prediction remained significant when thriving at work (the mediating variable), was introduced (β = 0.371, t = 4.772, P < 0.01). Psychological resilience significantly predicted thriving at work positively (β = 0.731, t = 20.779, P < 0.01), and thriving at work significantly predicted work performance positively (β = 0.256, t = 3.105, P < 0.05). The mediating effect size of thriving at work between psychological resilience and work performance was 33.49% (P < 0.05). Conclusion Thriving at work plays a partial mediating role between psychological resilience and work performance. The level of work performance among clinical nurses was relatively high. Nursing managers can enhance thriving at work by fostering psychological resilience among clinical nurses, thereby further improving their work performance to ensure high-quality and efficient nursing care.